2018
DOI: 10.1002/ange.201810410
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Rhodium(II)/Indium(III) Relay Catalysis for Tandem Insertion/Asymmetric Claisen Rearrangement

Abstract: The first example of catalytic insertion/asymmetric Claisen rearrangement tandem reaction of N‐sulfonyl‐1,2,3‐triazoles with allyl alcohol esters was achieved by bimetallic relay catalytic systems involving achiral rhodium salt and chiral N,N′‐dioxide–indium(III) complex. This manifold could overcome the limitation of single RhII catalysis, providing a straight and facile route to various enantioenriched β/γ‐amino acid derivatives in high yields (up to 99 %) with excellent diastereo‐ and enantioselectivities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 76 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In the absence of AuCl∙PPh 3 /AgOTf or In(OTf) 3 / L-PiEt 2 Me , only trace amount of the product 3aa was detected, which indicates that the two catalysts work cooperatively. N , Nʹ -dioxide/In(OTf) 3 crystal structure obtained in our previous study 49 showed that a OH-bridged dinuclear indium complex forms in the presence of H 2 O, in which N , Nʹ -dioxide coordinates to In(III) in a tetradentate manner. Nevertheless, the investigation of relationship between the e.e.…”
Section: Resultsmentioning
confidence: 93%
“…In the absence of AuCl∙PPh 3 /AgOTf or In(OTf) 3 / L-PiEt 2 Me , only trace amount of the product 3aa was detected, which indicates that the two catalysts work cooperatively. N , Nʹ -dioxide/In(OTf) 3 crystal structure obtained in our previous study 49 showed that a OH-bridged dinuclear indium complex forms in the presence of H 2 O, in which N , Nʹ -dioxide coordinates to In(III) in a tetradentate manner. Nevertheless, the investigation of relationship between the e.e.…”
Section: Resultsmentioning
confidence: 93%
“…On the basis of the mechanism of transition-metalcatalyzed enyne cycloisomerization, [7] our previous works, [10] and the determination of the absolute configuration of the products, [14] stereocontrol models for the [4+ +2] cycloaddition steps were proposed (Figure 1). Thec hiral N,N'-dioxide ligands coordinate to the Sc III or Ni II center in atetradentate manner to form octahedral structures.I nt he former case, chalcone 2 coordinates to the N,N'-dioxide-Sc III catalyst in amonodentate manner.T he catalyst activates the dienophile by decreasing the LUMO energy.S ubsequently,d ue to the steric hindrance of amide group of the ligand, the 1-methyl-2,3-disubstituted diene B could attack from b-Si face of a,bunsaturated ketone to form (4S,5 S,6 S)-3a ( Figure 1A).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[9] Recently,c hiral N,N'-dioxide-metal complex catalysts have proved to be good partners with several transition metals in relay catalysis. [10] Inspired by these works,weset out to combine the regiodiversity of 1,6-enyne cycloisomerization with the efficient enantioselection of chiral asymmetric Diels-Alder reactions catalyzed by N,N'-dioxide-metal complexes (Scheme 1B). In our proposal, different diene partners (B, D, and F)a re available in the presence of unique transitionmetal salts to perform the sequential [4+ +2] cycloadditions.…”
mentioning
confidence: 99%